An example of a field service plan for oceanographic submerged moorings - Schroeder, Katrin; Borghini, Mireno (Frontiers in Marine Science, 2024)
Oceanographic mooring missions are critical for advancing our understanding of the world’s oceans and their role in the broader Earth system. These missions rely on the deployment and maintenance of complex observing systems, comprising subsurface, profiling, and surface moorings, which are designed to collect valuable data from the ocean interior. The success of these missions depends on meticulous planning and strategic execution, which are facilitated by the use of Field Service Plans (FSPs). FSPs are comprehensive and adaptable planning tools that integrate safety measures, contingency plans, and timelines to ensure the successful and safe recovery, maintenance, and deployment of mooring systems. In this paper, we provide a comprehensive guide to drafting, implementing, and adapting FSPs tailored to the unique challenges posed by oceanographic mooring missions. We highlight the critical role of FSPs in optimizing safety, data quality, and mission success, while also underscoring the need for flexibility and adaptation. Our aim is to provide practical guidance and a template for researchers, expedition leaders, and institutions engaged in oceanographic research.